Multiple Myeloma in a Feline - Alberti, Taina dos Santos; Venancio, Fabiano da Rosa; Zamboni, Rosimeri; Scheid, Haide Valeska; Brunner, Carolina Buss; Raffi, Margarida Buss; Sallis, Eliza Simone Viégas (Acta Scientiae Veterinariae, 2020)
Background: Multiple myelomas (MM) are malignant neoplasms originating in the bone marrow plasmacytes, and are characterized by the presence of persistent hyperglobulinemia. Although they are rarely found in domestic animals, the canine species is most affected. In felines, they represent less than 1% of hematopoietic neoplasms, and mainly occur in older animals aged 10-12 years. The aim of the present study was to report a case of multiple myeloma, with extramedullary plasmocytosis in a feline. Case: A 3-year-old feline, female, mixed breed, with a history of apathy, anorexia, halitosis, and vomiting was referred to the Laboratório Regional de Diagnóstico (LRD) at the Universidade Federal de Pelotas (UFPel). Oral examination revealed a cyanotic oral mucosa and ulcerative lesions on the gingiva. The necropsy showed generalized lymphadenomegaly, splenomegaly, and hemorrhagic diathesis. Organ fragments were collected and fixed in 10% buffered formalin. After 48 h, the samples were cleaved, embedded in paraffin, and stained using the routine hematoxylin and eosin technique. Selected sections were subjected to immunohistochemistry (IHC) using the streptavidin-biotin method. The CD79a, CD138, CD3, and MUM1 antibodies were used. Histopathological evaluation of the bone marrow revealed hypercellularity with predominant round pleomorphic cells (90%), which presented an eccentric basophilic nucleus and abundant eosinophilic cytoplasm. The same neoplastic cells infiltrated the gingival mucosa, lymph nodes, spleen, liver, kidneys, heart, lungs, and brain. The IHC showed positive immunostaining for MUM1 and CD138 antibodies. Discussion: The diagnosis of MM in the present study was based on histopathology and by IHC. According to the literature, the presence of neoplastic plasmocytes in the bone marrow (>20%), osteolytic lesions, monoclonal gammopathy, and Bence-Jones proteinuria should be investigated in suspected MM cases. The presence of two or more of these characteristics is necessary for confirmed diagnosis. However, studies show that only 50% of felines with MM have two or more of these characteristics, with cell morphology and neoplastic infiltration in other organs being important parameters for the definitive diagnosis of MM in them. For MM diagnosis by IHC, CD79a, CD138, and MUM1 can be used. In this report, there was positive immunostaining for MUM1 and CD138, which allowed the exclusion of other neoplasms of hematopoietic origins. The origin of MM is unknown, but chronic immune stimulation is believed to be involved in humans. In felines, although infection by the feline immunodeficiency virus (FIV) and feline leukemia (FeLV) is commonly associated with the occurrence of lymphomas, the same is not described for MM. This was corroborated in the present study, since the animal in this report tested negative for FIV and FeLV. In cats, MM has no apparent predilection for race or sex, and mainly affects older animals (average age, 10 years). Although MM is rare, it has been described not only in this case, but also in young cats. The infiltration of neoplastic plasmacytes in the extramedullary tissues (extramedullary plasmacytosis) is observed more frequently in felines than in canines, and mainly occurs in the lymph nodes, spleen, and liver. In this case, there was disseminated extramedullary plasmacytosis involving multiple organs, such as the brain, lungs, heart, and kidneys. Persistent hyperglobulinemia is the main clinical manifestation of MM observed in 87.7% of cats with this neoplasm. However, this variation can also be observed in other pathologies, such as chronic lymphocytic leukemia, B cell lymphoma, primary macroglobulinemia, and chronic infections (e.g., ehrlichiosis, leishmaniasis, and heartworm disease). Hence, MM should always be considered as differential diagnosis when diagnosing the aforementioned diseases.